2013
DOI: 10.1158/2159-8290.cd-12-0418
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MYCN in Neuroblastoma by BET Bromodomain Inhibition

Abstract: Bromodomain inhibition comprises a promising therapeutic strategy in cancer, particularly for hematologic malignancies. To date, however, genomic biomarkers to direct clinical translation have been lacking. We conducted a cell-based screen of genetically-defined cancer cell lines using a prototypical inhibitor of BET bromodomains. Integration of genetic features with chemosensitivity data revealed a robust correlation between MYCN amplification and sensitivity to bromodomain inhibition. We characterized the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
565
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(620 citation statements)
references
References 46 publications
38
565
3
1
Order By: Relevance
“…Recent reports have shown that JQ1 suppresses growth of neuroblastoma in a set of in vivo models, including orthotopic transplantation of patient-derived xenografts and the TH-MYC mouse model (19,31). To determine the therapeutic effects of the TP-scaffold inhibitors in aggressive neuroblastoma, we established an s.c. xenograft model of MYCN-amplified neuroblastoma in immunocompromised mice using the SKNBE2 cell line.…”
Section: Intermolecular Contacts Of the Thienopyranone Substituents Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that JQ1 suppresses growth of neuroblastoma in a set of in vivo models, including orthotopic transplantation of patient-derived xenografts and the TH-MYC mouse model (19,31). To determine the therapeutic effects of the TP-scaffold inhibitors in aggressive neuroblastoma, we established an s.c. xenograft model of MYCN-amplified neuroblastoma in immunocompromised mice using the SKNBE2 cell line.…”
Section: Intermolecular Contacts Of the Thienopyranone Substituents Pmentioning
confidence: 99%
“…The second BD, BD2, selects for acetylated nonhistone proteins, though it is also capable of associating with acetylated histones H3 and H4. In the past few years, a number of BRD4-specific inhibitors have been developed, with some showing therapeutic effects in cancer models for NUT midline carcinoma, multiple myeloma, lymphoid leukemia, myeloid leukemia, and neuroblastoma (7,8,10,12,(18)(19)(20)(21)(22)(23).Because MYC itself has been proven to be a difficult therapeutic target, the PI3K-AKT-mTOR pathway and inhibition of PI3K kinase activity in particular has been a main focus of drug development (4, 24). However, inhibition of PI3K to enhance degradation of MYC provides only a limited therapeutic effect and is often followed by the development of resistance to the drug (25).…”
mentioning
confidence: 99%
“…The pathologic activation of MYCN plays a central role in high-risk neuroblastoma, while bromodomain-mediated inhibition of MYCN impaired growth and induced apoptosis in in vivo neuroblastoma models. 67 Histone modifying enzymes: Role in brain cancer therapy…”
Section: Neuroblastomamentioning
confidence: 99%
“…Recently, the bromodomain inhibitor, JQ1, was shown to target N-myc-amplified tumors by blocking N-myc-dependent transcription, impairing growth, and inducing apoptosis (86). Knockdown of the bromodomain protein BRD4 phenocopied these effects.…”
Section: Targeting N-mycmentioning
confidence: 99%